Chinese Immigrant Cultural Identity Acceptance in Turning Red Film - Attiba, Khoirotul (Vivid: Journal of Language and Literature, 2024)
This research aims to reveal the portrayal of Chinese cultural identity acceptance in Turning Red film. The writer employs qualitative research and content analysis as the method in conducting this research. It is also analyzed by using the theory of cultural identity by Stuart Hall. The result shows that Turning Red film portrays the third-generation Chinese immigrant as someone who preserves cultural values through her unwavering devotion to traditional Chinese eating practices, respect for her parents, preservation of the family’s great reputation, and regard for her ancestors. The film also portrays Meilin’s journey in accepting her Chinese roots. Meilin initially perceived the red panda as a curse due to its impact on her desire for independence and personal freedom. However, as time passed, Meilin’s acceptance grew due to the unwavering support of her peers and family. A moment of acceptance occurred when Meilin’s family ultimately settled with her choice to keep the red panda amidst chaotic arguments. As a conclusion, Meilin as a third-generation Chinese immigrant, proves that Stuart Hall’s theory of cultural identity, which states that identity is going to keep adapting to a variety of situations, is valid.